7(th) International Immunoglobulin Conference: Immunoglobulin in Clinical Practice - Shapiro, R S (Clin Exp Immunol, 2014)
Intravenous and subcutaneous immunoglobulins (IVIg and SCIg, respectively) are increasingly used in clinical practice, not only as replacement therapy but also for immunomodulation. Physicians have learned that primary immunodeficiency (PID) patients are susceptible to recurrent respiratory tract infections even when appropriately treated with immunoglobulin (Ig) therapy. Further investigation will establish whether a combined therapeutic approach including Ig dose optimization will prevent progressive lung disease in PID. The wear-off effects observed with IVIg can be minimized by adjusting the dosing regimen. It is also possible to avoid the cyclic wear-off following transition to SCIg administration. Consideration of benefit versus risk with Ig therapy includes evaluating the potential occurrence of thromboembolic and haemolytic events, which may be more frequent when Ig is administered in high doses and in the presence of pre-existing risk factors. The ability to select an administration method from IVIg, SCIg or hyaluronidase-facilitated SCIg infusions provides patient choice and alternatives if one or other administration route is not suitable for a patient. The evolution in indications, applications, and understanding of Ig therapy described here has reinforced the need for robust methods to prioritize Ig use.